CEBs: uma experiência brasileira: a utopia de ser Igreja libertadora e transformadora das estruturas sociais - Tracco, Celso Luiz (2014)
The main goal of this research is to study the evangelization model of urban performed by the Basic Ecclesial Communities. During the European occupation of the American continent, especially in Brazil, the metropolis carried out a violent imposition of habits, culture, religion and political system on their colonies. The process of evangelization was very much alike, compulsory and with no room for discussions, even though there was absolutely no concern in creating a deep general knowledge of faith. In Brazil, during the colonial and imperial periods, all persons were born catholic by imperial decree. This study assumes that religion must be seen as a part of a social, political and economic context, hence, the research includes the socioeconomic and political building of the Brazilian society. The evangelization model proposed by the Basic Ecclesial Communities is a Brazilian phenomenon, typical of the country s culture and with its origins in the lower and excluded classes. This model would not be possible without the social changes and the opening of the church as an institution to those changes, which took place in Brazil during the mid-20th century. A new, groundbreaking, form of evangelization was only possible thanks to the initiative of a clergy concerned with the poor social conditions of its people. This study intends to understand the scope of this evangelizing method and its possible extent nowadays. The evangelization led to a reflection of the existential reality and also to a political questioning, until then dominated by the Brazilian elites. This political extrapolation from the traditional channels of the church was strongly criticized by traditionalist sectors of power. Also, the new evangelizing experience was put under judgment by the ecclesiastical authorities. This study intends to investigate if the Basic Ecclesial Communities model - a new model of church, a people s church has a place in the evangelization of today s society